Assessment of the Chesapeake Bay watershed socio-ecological system through the Circles of Coastal Sustainability framework - Leyva Ollivier, María Esther; Newton, Alice; Kelsey, Heath (Frontiers in Water, 2024)
The concern with preserving natural resources for the future has been capturing global attention due to the state of decline of productive ecosystems. To preserve these ecosystems, the concept of sustainable development was defined. The Chesapeake Bay, a large estuary located on the mid-Atlantic coast of the United States of America, is such a productive ecosystem. The natural resources support thousands of animals, plant species, and the surrounding human population. However, there has been continued pressure on natural resources and ecosystem services from human activities. Institutional restoration and management efforts have been extensive, generating organizations, agreements, regulations, and projects, among others. This research aims to assess the Chesapeake Bay's sustainability in four domains: environment, social, economy, and governance, using the Circles of Coastal Sustainability methodology. Each of the four domains has five categories, and each category is evaluated by the authors' expert judgment using indicators related to the socio-ecological system and the definition of sustainable development. The article proposed a global sustainability score developed by a literature review of sustainability evaluated through the expert judgment of the authors. The results obtained from the framework gave a "Satisfactory" score to the overall system, which means that the system has degradation problems with bridges and barriers to achieve sustainable development. The environment, economic, and governance domains obtained the same score. Meanwhile, the social domain obtained a "Poor" score. The categories range between "Excellent" and "Poor" scores. The "Excellent" score was obtained by one category (i.e.,Organization). The "Poor" score was obtained by five categories across the domains (i.e.,Social benefits, Demographic, Identity, Security, Economy well-being). The assessment results gave a general foundation of the management bridges and barriers for sustainable development. The barriers were used to discuss new bridges summarized in holistic management proposals. The framework is a tool in progress to communicate to various actors the current sustainability development with the available information; provide a holistic system view; and find knowledge gaps in the research of a system. Likewise, the framework and assessment can be complemented, adapted, refined, and improved with each application as part of an adaptive management iterative cycle.